The effects of structural confinement and thermal profiles on propagating spin waves - Riley, Grant Alston, author; Buchanan, Kristen S., advisor; Neilson, James, committee member; Krueger, David, committee member; Patton, Carl, committee member (Colorado State University. Libraries, 2018)
Spintronics is a growing field that relies on the spin degree of freedom in the form of spin currents instead of electronic charge to transmit and process information. There are many advantages to spin-based devices including scalability, a wide range of host materials including insulators, and almost no energy loss due to Joule heating. Spin angular momentum can be transmitted in the form of spin-polarized currents that flow through a metal, pure spin currents, or in the form of spin waves, disturbances in the magnetization state that can propagate and hence can carry energy. If such a spin-based paradigm is to be realized, there are many open questions that must be addressed. Two questions of particular importance are: how can short wavelength spin waves that are needed for information transmission be controllably generated? and once generated, how can these spin waves be modified and controlled? This thesis focusses on answering both of these questions through the investigation of spin waves in two different types of samples, patterned microstructures and thin continuous films, performed using Brillouin light scattering (BLS) spectroscopy. In the first experiment, the possibility of generating short wavelength spin waves by dynamically exciting a non-uniform magnetic state called the antivortex (AV) in a Permalloy microstructure is explored. Frequency scans were performed to identify a spectrum of high-frequency modes of the AV state. These modes were then individually mapped out by pumping at the frequency of the mode and performing spatially-resolved BLS scans. Comparing the experimental results with dispersion curves and micromagnetic simulations reveals that some of most prominent modes involve coupling of the AV dynamics to propagating spin waves in the adjacent nanowires highlighting the fact that the local magnetization state has a significant effect on the spin wave dynamics. Due to the natural way that an antivortex state can be incorporated into a nanowire network, this spin configuration may be useful as a means to generate or control spin waves for applications. In the second study we explore the possibility of modifying the propagation characteristics of both spin waves and spin caustic beams, which could be highly useful in spin-wave-based logic devices, using non-uniform thermal gradients up to 4.5 K/mm. These experiments were performed in a yttrium iron garnet (YIG) thin film - a model system for studying spin waves due to extremely low damping characteristics. An intricate diamond-shaped propagation pattern was observed and explained using the dispersion manifold for the YIG film and considering the range of wavevectors excited by the antenna. Significant modifications to the propagation characteristics such as beam angle, temporal pulse shape, mode profiles, and group velocity were observed as spin waves travelled into heated regions. These results will serve to broaden the understanding of how heat can be used to affect and control spin waves.
Keywords: magnetics; spin waves; magnetization dynamics; Brillouin light scattering